The ‘educational destinations’ of Generation X: outcomes and inequalities in a generational perspective - Giancola, Orazio; Bonanni, Matteo (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The analysis of inequalities over time, especially those related to education, has been a relevant topic in the social sciences. This study proposes a diachronic approach based on cohorts-generations from the post- World War II period to the present, showing the double trend on the one hand of increasing educational levels of the Italian population and on the other of how persistent gaps between social classes have remained relatively stable despite increased participation in the educational system. The article then focuses on the so-called Generation X, since it can be considered the generation that first experienced the slowdown of an economic development that was considered unlimited and inevitably positive. Finally, an attempt is made to initiate a reflection on the educational destinies of future generations in light of the paradigmatic changes that have occurred over time.